Community Coffee Plantations From a Value-Added Perspective in Empat Lawang Regency - Novi Apriani; Sisvaberti Afriyatna; Puri Pratami Ardina Ningrum (Journal of Global Sustainable Agriculture, 2024)
The study analyze the added value of smallholder coffee added to ground coffee. Because coffee is one of the plantation commodities that has high economic potential, the added value obtained by farmers is often not in accordance with estimates. This study applies quantitative descriptive analysis. Coffee farmers and business actors, consisting of forty farmers, were randomly selected through a simple random sampling method. To analyze the added value data, the Hayami Method was used to collect data through interviews and direct observation of farmers. The results of the study showed that the process of processing green coffee beans (greenbeans) into ground coffee produced an added value of IDR 74,285.71/kg with a value added ratio of 87.39%. However, there are several obstacles, such as dependence on institutional actors, limited market access, and technology.